GPi vs STN deep brain stimulation for Parkinson disease: Three-year follow-up. (23rd February 2016) - Odekerken, Vincent J.J.; Boel, Judith A.; Schmand, Ben A.; de Haan, Rob J.; Figee, M.; van den Munckhof, Pepijn; Schuurman, P. Richard; de Bie, Rob M.A.
Abstract : Objective: To compare motor symptoms, cognition, mood, and behavior 3 years after deep brain stimulation (DBS) of the globus pallidus pars interna (GPi) and subthalamic nucleus (STN) in advanced Parkinson disease (PD). Methods: Patients with PD eligible for DBS were randomized to bilateral GPi DBS and bilateral STN DBS (1:1). The primary outcome measures were (1) improvement in motor symptoms in off-drug phase measured with the Unified Parkinson Disease Rating Scale (UPDRS) and (2) a composite score for cognitive, mood, and behavioral effects, and inability to complete follow-up at 36 months after surgery. Results: Of the 128 patients enrolled, 90 were able to complete the 3-year follow-up. We found significantly more improvement of motor symptoms after STN DBS (median [interquartile range (IQR)] at 3 years, GPi 33 [23–41], STN 28 [20–36], p = 0.04). No between-group differences were observed on the composite score (GPi 83%, STN 86%). Secondary outcomes showed larger improvement in off-drug functioning in the AMC Linear Disability Scale score after STN DBS (mean ± SD, GPi 65.2 ± 20.1, STN 72.6 ± 18.0, p = 0.05). Medication was reduced more after STN DBS (median levodopa equivalent dose [IQR] at 3 years, GPi 1, 060 [657–1, 860], STN 605 [411–875], p < 0.001). No differences in adverse effects were recorded, apart from more reoperations to a different target after GPi DBS (GPi n = 8, STN n = 1). Conclusions: Off-drug phase motor symptoms and functioning improve more after STN DBS than after GPi DBS. No between-group differences were observed on a composite score for cognition, mood, and behavior, and the inability to participate in follow-up. Classification of evidence: This study provides Class II evidence that STN DBS provides more off-phase motor improvement than GPi DBS, but with a similar risk for cognitive, mood, and behavioral complications.